Numerical study of stress distribution and crack coalescence mechanisms of a solid containing multiple holes. (October 2015) - Wong, Robina H.C.; Lin, P.
Abstract: This study investigated the change of stress with crack development, using the numerical code RFPA 3D, so as to understand the crack coalescence mechanisms occurring within a heterogeneous solid containing multiple holes loaded in a state of uniaxial compression. A full discussion is presented on a statistical analysis of observed microcracks data, and on the appropriate parameter selection based on those microcrack statistics. The simulated peak stress results and coalescence patterns using the selected parameters were found to closely resemble previous experimental observations. A full investigation and discussion of the stress distributions around holes during the crack growth and coalescence processes is presented for heterogeneous sample cases. Under applied loading, crack initiation, growth direction and coalescence pattern are strongly influenced by the shape of the interaction tensile zone formed between holes. Acoustic emission (AE) analysis in relation to the numerical simulations indicates that no case of pure tensile crack coalescence occurs between holes. Three modes of coalescence are classified: T s mode (tensile mode coalescence with shear), M T mode (mixed mode coalescence with tensile mode dominant) and M mode (mixed mode coalescence). The crack coalescence mechanisms and patterns were further investigated by changing the parameters of normalized bridge length ( d/r ), bridge angle β and number of holes. A precise crack coalescence criterion is proposed. Highlights: Statistical analysis from the observed microcracks data for selecting the appropriate Weibull parameter is fully discussed. Stress distribution around the holes and the shape of the stress interaction zone is strongly influenced by distribution of holes. The effect of bridge length d/r and bridge angle β on coalescence mechanisms is investigated and discussed comprehensively. Simulated acoustic emission (AE) analysis indicates no purely tensile cracks coalescence pattern occurs between holes. A precise crack coalescence criterion is proposed.